2022
DOI: 10.3847/psj/abe3fd
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Machine-learning Atmospheric Retrieval via a Neural-network Surrogate Model for Radiative Transfer

Abstract: Atmospheric retrieval determines the properties of an atmosphere based on its measured spectrum. The low signal-to-noise ratios of exoplanet observations require a Bayesian approach to determine posterior probability distributions of each model parameter, given observed spectra. This inference is computationally expensive, as it requires many executions of a costly radiative transfer (RT) simulation for each set of sampled model parameters. Machine learning (ML) has recently been shown to provide a significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 77 publications
(73 reference statements)
1
24
0
Order By: Relevance
“…This comes however at the expense of posterior accuracy, as the resulting parameter distributions are either not true posteriors (Márquez-Neila et al 2018), or are enforced to follow a multivariate Gaussian distribution (Zingales & Waldmann 2018;Nixon & Madhusudhan 2020;Ardévol Martínez et al 2022). Another approach is to use machine learning to generate more informed, narrower priors (Hayes et al 2020), or even to replace the exoplanet atmosphere simulator by a surrogate model (Himes et al 2022). These methods have the potential of providing more accurate posterior distributions, but at the expense of a more modest improvement in terms of inference time.…”
Section: Introductionmentioning
confidence: 99%
“…This comes however at the expense of posterior accuracy, as the resulting parameter distributions are either not true posteriors (Márquez-Neila et al 2018), or are enforced to follow a multivariate Gaussian distribution (Zingales & Waldmann 2018;Nixon & Madhusudhan 2020;Ardévol Martínez et al 2022). Another approach is to use machine learning to generate more informed, narrower priors (Hayes et al 2020), or even to replace the exoplanet atmosphere simulator by a surrogate model (Himes et al 2022). These methods have the potential of providing more accurate posterior distributions, but at the expense of a more modest improvement in terms of inference time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Himes et al (2022) presented a novel machinelearning approach to exoplanet atmospheric retrieval, where the radiative transfer forward model is replaced with a neural network (NN) surrogate model. We found that this approach achieves similar quantitative results as the classical approach but at a fraction of the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…Classical inversion methods extensively used in analyzing infrared spectra from remote sensing of the Earth and solar system planets are described in Hanel et al (2003) and are based on linearizing the problem. More recent numerical approaches include sampler-based retrievals (Lee et al 2012;Line et al 2013bLine et al , 2013aWaldmann et al 2015;Lavie et al 2017;Blecic et al 2022;Cubillos et al 2022;Harrington et al 2022) and various machine learning (ML) techniques (Waldmann 2016;Márquez-Neila et al 2018;Soboczenski et al 2018;Zingales & Waldmann 2018;Cobb et al 2019;Fisher et al 2020;Himes et al 2020a;Oreshenko et al 2020;Himes et al 2020b;Guzmán-Mesa et al 2020;Nixon & Madhusudhan 2020;Yip et al 2021;Ardevol Martinez et al 2022;Himes et al 2022; for a recent comparative review, see . The main disadvantages of the numerical ML approach are: (i) the ML model is in principle a black box that hides the relevant physics and is not easily interpretable (Nixon & Madhusudhan 2020;Yip et al 2021); (ii) the ML model does not learn directly the relevant physics, but only the (finite amount of) data generated by the forward model, which introduces additional uncertainties during the training process (Matchev et al 2022a).…”
Section: Introductionmentioning
confidence: 99%